(untitled) (Cadernos de Ética e Filosofia Política, 2020)
This text intends to analyse the meaning of the concept negation of will in the Schopenhauer’s ethics. We can understand the Schopenhauer’s thought in two different moments. In the First, the philosopher shows his pessimism about the life. In the second moment he presents the search for the solution to the problems of the world’s sorrow. The negation of will (or negation of life – it is the same, in the Schopenhauer’s philosophy), presented for the philosopher as the redemption (Erlösung) of the moral’s problem, introduces us in an aspect too much tragic of the reality: the nihilism.